Comparative evaluation of intracorporeal lithotripsy techniques during ureteroscopy: a clinical experience - Trivedi, Pankaj (International Surgery Journal, 2020)
Background: The objective of the study was to compare pneumatic lithotripsy and laser lithotripsy techniques for safety, efficacy, and complications in the management of ureteric stone. Methods: Patients underwent ureteroscopy for ureteral stones in a tertiary care teaching hospital were divided into 2 groups of 50 each. Group 1 patients underwent pneumatic lithotripsy and group 2 underwent holmium:yttrium-aluminium-garnet (Ho: YAG) laser lithotripsy. Both the groups were compared regarding demographic characteristics, stone dimensions, number of stones, operative time, stone migration rate, application of post-operative double J (DJ) stent, complications, and stone free rate. Results: Mean age of the patients in the group 1, and group 2 were 45.74±18.49, and 44.5±14.33 years, respectively (p=0.709). There was no significant difference in male to female ratio in both groups. Total operative times were found 29.12±10.83 min, and 28.44±7.49 min in the group 1 and group 2, respectively which was statistically non-significant (p=0.716). The stone free rate was 100% and 98% in group 1 and 2 respectively (p=0.130). Stone migration was also found in 5 (10%) patients in the group 1 and 1 (2%) in group 2 which was found statistically significant (p=0.037). Mucosal damage was found 3 (6%) in laser group as compared to 1 (2%) in pneumatic group. No significant difference between complications was seen in both the groups. Conclusions: This study concluded that pneumatic lithotripsy and laser lithotripsy have similar efficacy in terms of operative time, success rate and hospital stay time. However, stone migration rate was significantly more in pneumatic lithotripsy.